2007
DOI: 10.1186/1750-1172-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic neurological syndromes

Abstract: Paraneoplastic neurological syndromes (PNS) can be defined as remote effects of cancer that are not caused by the tumor and its metastasis, or by infection, ischemia or metabolic disruptions. PNS are rare, affecting less than 1/10,000 patients with cancer. Only the Lambert-Eaton myasthenic syndrome is relatively frequent, occurring in about 1% of patients with small cell lung cancer. PNS can affect any part of the central and peripheral nervous system, the neuromuscular junction, and muscle. They can be isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
242
0
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 74 publications
3
242
0
21
Order By: Relevance
“…Like other types of CRMP family proteins, CRMP5 is expressed throughout the nervous system (Wang and Strittmatter, 1996;Fukada et al, 2000). Interestingly, anti-CRMP5 antibody is often detected in serum of patients with subacute cerebellar ataxia, and has been recognized as one of the main antibodies associated with paraneoplastic syndromes (Yu et al, 2001;Cross et al, 2003;Pittock et al, 2004;Honnorat and Antoine, 2007). However, the in vivo roles of CRMP5 remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Like other types of CRMP family proteins, CRMP5 is expressed throughout the nervous system (Wang and Strittmatter, 1996;Fukada et al, 2000). Interestingly, anti-CRMP5 antibody is often detected in serum of patients with subacute cerebellar ataxia, and has been recognized as one of the main antibodies associated with paraneoplastic syndromes (Yu et al, 2001;Cross et al, 2003;Pittock et al, 2004;Honnorat and Antoine, 2007). However, the in vivo roles of CRMP5 remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6,13,14 CRMP-5 is expressed in the optic nerve, neurons of the central and peripheral nervous systems, oligodendrocytes, and the cytoplasm of SCLC cells. 5,6,10,11,[13][14][15] It has been suggested that autoantibodies generated against the neoplastic CRMP-5 react as a host immune response to normal tissues, resulting in various neuronal disorders.- 6,10,16 In our case, bilateral meningeal enhancement of the optic nerve was evident on MRI, indicating that the main pathogenesis of the optic neuropathy was bilateral perioptic neuritis due to the involvement of oligodendrocytes around the optic nerve. This cause is consistent with preserved central visual acuity, prominent disc swelling, and prompt disappearance of disc swelling in response to the cancer treatment.…”
Section: Discussionmentioning
confidence: 64%
“…1,2 Most PON patients exhibit many neurological symptoms, including ophthalmoplegia, cerebellar ataxia, seizures, dementia, and various sensory and/ or motor abnormalities. 1,[3][4][5] The various neurological symptoms are believed to be caused by an antitumour immune response 3,6 associated with an increased level of autoantibodies against collapsing response-mediating protein-5 (CRMP-5), 4,5,[7][8][9] which is expressed in the optic nerve, neurons of the central and peripheral nervous systems, oligodendrocytes, the cytoplasm of small cell lung carcinoma (SCLC) cells, or thymomas.- 5,6,[9][10][11] Only a few studies have reported anti-CRMP-5 antibody-positive PON cases that presented with optic neuropathy as the only clinical symptom. Magnetic resonance imaging (MRI) of these cases has been reported as normal, 8,12 or involving unilateral optic nerve involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Все ПНС разделены на классические и неклассические. Классические ПНС (паранеопластическая моз-жечковая дегенерация, лимбический энцефа-лит, дерматомиозит, полинейропатии, синдром опсоклонус-миоклонус, миастенический синдром Ламберта-Итона, хроническая гастроинтести-нальная псевдообструкция), как правило, ассо-циированы со злокачественными новообразова-ниями, тогда как крайне редкие неклассические (паранеопластическая хорея, синдром «ригидного человека») выявляются и при других заболеваниях [2][3][4].…”
Section: Introductionunclassified